2013
DOI: 10.1007/s11547-013-0323-6
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic impact of 18F-FDG PET/CT in recurrent differentiated thyroid carcinoma

Abstract: PET/CT can help select patients, who might benefit from a tailored therapy by improving the detection of local recurrences not apparent on neck US or metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In the follow‐up of DTC, FDG PET/CT has a distinct role in the follow‐up of RAI negative thyroid cancer lesions with an elevated Tg level and has an impact on treatment planning and prognosis . Although there is substantial literature supporting the use of FDG PET/CT scan in patients with elevated Tg levels, there is no clear mention of the optimal timing and frequency of PET/CT studies in DTC .…”
Section: Discussionmentioning
confidence: 99%
“…In the follow‐up of DTC, FDG PET/CT has a distinct role in the follow‐up of RAI negative thyroid cancer lesions with an elevated Tg level and has an impact on treatment planning and prognosis . Although there is substantial literature supporting the use of FDG PET/CT scan in patients with elevated Tg levels, there is no clear mention of the optimal timing and frequency of PET/CT studies in DTC .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have demonstrated a change in therapy management using PET/CT. [ 20 21 ] Although we did not intend to document it, we observed that many patients with thyroid bed or cervical lymph node recurrence had coexisting mediastinal lymphadenopathy or lung metastases that excluded radical local treatments.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 18 19 ] Few studies have demonstrated that PET/CT may change therapy management in a substantial number of patients. [ 20 21 ] DTC usually spreads to cervical and thoracic regions and distant bones with relative sparing of other visceral organs. The prevalence of metastasis to the other sites is low.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, current applications extend to disease extension, including the detection of undifferentiated metastases (3), guidance of therapy assessments and prediction of prognosis (4)(5)(6). Some studies have shown that 18 F-FDG PET and 18 F-FDG PET/CT can induce changes in clinical management plans in 10-78% of patients with DTC (7)(8)(9)(10)(11)(12), thereby improving clinical judgment. In the Brazilian population, there has been only one study using 18 F-FDG PET/CT in thyroid cancer patients with negative WBS and positive sTg in a small patient sample (13).…”
Section: Introductionmentioning
confidence: 99%